729 Endoluminal Vacuum Therapy in the Management of Boerhaave Syndrome: A Case Series. (19th August 2022) - Soussi, D; Helmi Ahmad Alharahsheh, B; Stevens, S; Boshier, P; Karim, S; Hoare, J; Direkze, N; Ekpe, J; Peters, C
Abstract: Background: Boerhaave syndrome is a rare condition associated with poor prognosis: high morbidity and mortality. Prompt intervention greatly improves outcomes, with surgery being the mainstay of management. Recent advances in therapeutic endoscopy have led to increasing interest in endoluminal vacuum therapy (EVT). EVT is a minimally invasive technique, allowing wound debridement and drainage, and granulation tissue formation. EVT has been associated with excellent clinical outcomes, including lower mortality rates when compared to surgery and stenting. EVT has been adopted into practice across Europe, however, only two cases have been reported in the UK. We report three cases of Boerhaave syndrome, successfully managed with EVT, using the EsoSPONGE ® (B.Braun, Medical Ltd, Sheffield, UK). Method: EVT involves the placement of a polyurethane sponge into the wound cavity. The cavity is initially assessed endoscopically before an overtube is introduced. The sponge is pushed into the cavity through the overtube, and the overtube is removed. Sponge position is confirmed and adjusted if necessary. The sponge is connected via a trans-nasal drain to continuous negative pressure suction and is changed every 3–5 days. Results: Having been deemed surgically unfit, all three patients were referred for EVT, using the EsoSPONGE. All patients made excellent recovery and were discharged home. Conclusions: EVT is an effective management strategy for surgically unfit Boerhaave syndrome patients. EsoSPONGE use aided drainage of the septic focus and closure of the defect, leading to complete recovery. Our findings support the existing evidence that EVT is a promising solution for Boerhaave syndrome.